Blue and red LEDs modulate polyphenol production in Precoce and Tardiva cultivars of Cichorium intybus L. - Felicia Menicucci; Giovanni Marino; Fabiano Sillo; Andrea Carli; Luana Beatriz dos Santos Nascimento; Luana Beatriz dos Santos Nascimento; Cassandra Detti; Mauro Centritto; Cecilia Brunetti; Cecilia Brunetti; Raffaella Maria Balestrini (Frontiers in Plant Science)
IntroductionPlant growth and metabolism can be optimized by manipulating light intensity and wavelength. Since the use of light-emitting diodes (LEDs) allows easy regulation of the light spectrum, LEDs technology is largely tested to produce high-quality food. Red leaf chicory is a horticultural plant of high commercial value, rich in vitamins, minerals and phytochemical compounds with bioprotective and antioxidant roles.MethodsCichorium intybus L. (Asteraceae family) seedlings of the cultivar Rossa di Treviso Precoce and Rossa di Treviso Tardiva were cultivated under blue and red LEDs for three to four weeks, whereas white LEDs, proving full visible light spectrum, were supplied as control. The leaf polyphenols were characterized and quantified by HPLC-DAD-Q-ToF analysis, the leaf chlorophyll content was measured using a handheld optical analyzer and the photosystem II efficiency was assessed with a porometer-fluorometer.ResultsThe PS II efficiency decreased in response to red LEDs treatment only. The highest levels of polyphenol and chlorophyll content were registered in response to blue LEDs exposure in both cultivars. The Rossa di Treviso Tardiva also exhibited a significant accumulation of polyphenols under red LEDs compared to white LEDs. The polyphenolic composition of the two cultivars significantly changed depending on the type of LEDs used. The leaf extracts of plants grown under red LEDs showed a prevalence of kaempferol 3-O-glucuronide, whereas a predominance of quercetin derivatives was found in response to white and blue LEDs. The comparison of the two cultivars revealed that the Rossa di Treviso Precoce was characterized by a higher content of polyphenols, independently of the type of LEDs.DiscussionSpecies-specific protocols are required for producing high-content nutrient vegetables. In our study, red LEDs induced a completely different leaf polyphenol composition than blue and white LEDs, pointing out that an accurate light spectrum selection is crucial for shaping plant metabolism. Blue LEDs improved the content of photosynthetic pigments and induced an accumulation of highly antioxidant polyphenols in both Rossa di Treviso Precoce and Tardiva C. intybus cultivars, emerging as a valuable tool for improving their nutraceutical content.